Transfer of Cyclobenzaprine into Human Milk and Subsequent Infant Exposure. (August 2019) - Burra, Bhaskari; Datta, Palika; Rewers-Felkins, Kathleen; Baker, Teresa; Hale, Thomas W.
Introduction: Cyclobenzaprine is a skeletal muscle relaxant primarily used in the treatment of pain. Its use during lactation is a matter of concern as its level of exposure to infants through human milk is still unknown. Main issue: The aim of this study was to determine cyclobenzaprine concentrations in the milk samples collected from two lactating mothers. Management: The present study describes the analysis of cyclobenzaprine in human milk using liquid chromatography mass spectrometry, which determined the drug concentration-time profiles in human milk. Conclusion: This study shows low levels of concentrations of cyclobenzaprine in human milk with calculated relative infant dose of 0.5%. However, due to the sedative properties of cyclobenzaprine, regular clinical assessment of the infant is recommended to evaluate for long-term effects.